The methods to identify compacted saturated hydrocarbon rocks (on the example of southern Dnieper-Donets basin margin - Хроль, В. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
Formulation of the problem. The article focuses on the study of one variety of unconventional sources of saturated hydrocarbon compacted rocks. It is known that in the last 5-7 years Ukraine started to pay close attention to the issue of unconventional hydrocarbons. The vector of additional prospecting industry refocused on existing fields of implementation and the involvement of new, advanced technologies. Following the example of countries that have successfully extracted gas and oil from compacted rocks we can say with confidence that the chosen direction is the most relevant and promising for our country. The purpose of the article. To survey the results of Pereschepynskii-Ulyanivskii deposits, and considering the research results of leading countries to show the feasibility study of compacted deep saturated hydrocarbon species within Dnieper-Donets basin. Methods. In writing this article the authors used the experience of domestic and foreign authors as well as their own research data. Results. In the early 70’s XX century the US has carried out exploration work during which four large pools of compacted rocks were revealed. Due to the rapid growth of steel production the USA became a world leader with almost 40% of gas accounted for non-traditional sources (25% - gas condensed explosive rocks). Basic research methods are: analysis of material exploration, geological and geophysical surveys; industrial logging operations; tectonic and stratigraphic knowledge of the region; petrophysical features of rocks; preliminary, operational, detailed studies of core and sludge wells; the reinterpretation of GDS and other materials. For example, the survey results of Pereschepynskii and Ulyanovskii deposits located in the southern area alongside Dnieper-Donets depression (PPD) suggest that prospective compacted rock strata are associated with traditional anticlinal traps and are in direct contact with intervals of productive strata. The area has prospects for industrial flow of gas from reservoir compaction. The highest probability to find hydrocarbons in compacted rocks can be expected with rhythmic siltstone layering. In their further study gas-saturated rocks should be considered comprehensively. Scientific novelty and practical significance. Earlier studies of dense sand strata in siltstone of Pereschepynskii and Ulyanivskii areas were not considered as potential sources of hydrocarbons. We can assume that most likely carbon deposits should be considered regionally. Distribution of hydrocarbons was traced both horizontally and vertically. It is possible that in the future there will be increase in the number of carbon productive horizons in the deposits. Upon confirmation of carbon saturation in the thick compacted rocks they can be considered and recommended as a potential source of siltstone gas.